2019
DOI: 10.14720/aas.2019.114.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a new non-toxic water-soluble selenorganic substance on antioxidant protection and development of seedlings of oilseed radish (Raphanus sativus L. var. oleiferus Metzg.)

Abstract: <p class="Default"><strong> </strong></p><p class="Default">The effect of 2,6-dipyridinium selenabicyclo[3.3.1]nonandibromide (996 zh) on the level of lipid peroxidation (LPO), on the activity of glutathione reductase (GR) and on the morphometric parameters of oilseed radish seedlings under normal conditions and under stress (200 mmol NaCl) has been studied. It has been established that the substance 996 zh at a concentration of 100 μm exerted an antioxidant effect reducing the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Over the past few years, the cultivation of plants has been facing a number of challenges, including a dramatic increase in temperatures, lack of soil water, and the need for more resistant and hardy plants, which grow even under the harshest conditions. It is therefore vital to minimise the time required for the growth of planting material, which can be done using growth and germination stimulants, including synthesised chemical compounds Pentelkina, 2003;Vasin et al, 2008Vasin et al, , 2009Ostroshenko and Ostroshenko, 2011;Schuchka, 2006;Baranova, 2013a;Khodaei-Joghan et al, 2018;Nesterkina et al, 2019) and other original modes (Shibaeva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, the cultivation of plants has been facing a number of challenges, including a dramatic increase in temperatures, lack of soil water, and the need for more resistant and hardy plants, which grow even under the harshest conditions. It is therefore vital to minimise the time required for the growth of planting material, which can be done using growth and germination stimulants, including synthesised chemical compounds Pentelkina, 2003;Vasin et al, 2008Vasin et al, , 2009Ostroshenko and Ostroshenko, 2011;Schuchka, 2006;Baranova, 2013a;Khodaei-Joghan et al, 2018;Nesterkina et al, 2019) and other original modes (Shibaeva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We studied nucleophilic substitution reaction of bromine in compound 2 by pyridine [ 69 , 70 ]. Dipiridinium salt, 2,6-dipyridiumyl-9-selenabicyclo[3.3.1]nonane dibromide, was obtained in near quantitative yield [ 69 , 70 ].…”
Section: Introductionmentioning
confidence: 99%
“…We studied nucleophilic substitution reaction of bromine in compound 2 by pyridine [ 69 , 70 ]. Dipiridinium salt, 2,6-dipyridiumyl-9-selenabicyclo[3.3.1]nonane dibromide, was obtained in near quantitative yield [ 69 , 70 ]. The biological activity of this compound as a medicine for metabolic correction in the vaccination process and its effect on immunogenesis were studied [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that water soluble pyridinium salt 1 derived from 2,6-dibromo-9-selenabicyclo[3.3.1]no­nane is promising for metabolic correction after vac­cina­tion [ 10 , 11 ]. Administration of compound 1 in experimental animals significantly inhibits the devel­op­ment of pathological responses after injection of a tularemia vaccine and reduces the reactogenicity of brucellosis vaccine [ 10 ].…”
mentioning
confidence: 99%
“…Administration of compound 1 in experimental animals significantly inhibits the devel­op­ment of pathological responses after injection of a tularemia vaccine and reduces the reactogenicity of brucellosis vaccine [ 10 ]. Moreover, compound 1 is non­toxic [ 10 ], and it does not exhibit glutathione peroxidase-like activity, i.e., it acts as a catalyst for the decom­position of peroxide compounds in the organism [ 11 ].…”
mentioning
confidence: 99%